The influence of local resistance on the accuracy of the air velocity measurement with the air torque position damper - Siniša Bikić; Nikola Vukadin; Milivoj Radojčin; Ivan Pavkov; Rafat Al Afif (International Journal of Thermofluids)
Measuring airflow rate is essential in various industrial and engineering applications. The air torque position (ATP) damper is one device employed for this purpose, indirectly measuring air velocity by assessing the torque exerted by airflow on the blades and their position. This study aims to evaluate the impact of local resistance on the accuracy of airflow velocity measurements using the ATP damper. A laboratory ATP damper with a 250 mm x 250 mm square cross-section was utilized. Three damper designs with flat blades were tested: a single blade, two cross-guided blades, and two blades with one fixed horizontally. Two damper locations were considered: at the end of the ductwork and in the middle, with straight sections both upstream and downstream. A steel sheet reducing the duct's cross-sectional area by 50 % served as a local obstacle, positioned 0.5 m upstream and downstream of the damper. Two independent measurement series were conducted for each setup: one without the local resistance and one with it. Results indicated that local resistance upstream of the damper significantly affects airflow velocity measurement accuracy when the damper's angle of attack is ≤ 30°. This effect was consistent across all damper locations and designs tested. In order to determine the necessary length of straight duct sections without presence of local resistances upstream and downstream the damper, it is necessary in the future to continue research the impact of the presence of local resistance to the accuracy of air flow rate measurements using ATP dampers.